2020
DOI: 10.1136/bmjopen-2020-036936
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study on the pharmacokinetic properties of the Irrua ribavirin regimen used in routine clinical practice in patients with Lassa fever in Nigeria

Abstract: IntroductionLassa fever (LF) is a severe and often fatal systemic disease in humans and affects a large number of countries in West Africa. Treatment options are limited to supportive care and the broad-spectrum antiviral agent ribavirin. However, evidence for ribavirin efficacy in patients with LF is poor and pharmacokinetic (PK) data are not available.Irrua Specialist Teaching Hospital (ISTH) developed an intravenous ribavirin regimen different to the WHO recommendation. Apart from a lower total daily dose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…A limitation of this study is that the Irrua regimen used in routine care was adapted individually by treating physicians, including a variability in the decrease of dosing to 12.5 mg/kg between days 6 and 8. At the time of protocol development, 100 mg/kg loading dose on the first day of treatment (if total dose >7 g, then 2/3 administered at presentation and 1/3 8 hours later) followed by 25 mg/kg once daily from days 2 to 5 and 12.5 mg/kg once daily from days 6 to 10 were a widely used variation that is reflected in Figure 2 and in the published study protocol [ 13 ]. The study team did not interfere with treatment decisions of the treating physician including drug dosage and schedule because of the observational nature of the study design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limitation of this study is that the Irrua regimen used in routine care was adapted individually by treating physicians, including a variability in the decrease of dosing to 12.5 mg/kg between days 6 and 8. At the time of protocol development, 100 mg/kg loading dose on the first day of treatment (if total dose >7 g, then 2/3 administered at presentation and 1/3 8 hours later) followed by 25 mg/kg once daily from days 2 to 5 and 12.5 mg/kg once daily from days 6 to 10 were a widely used variation that is reflected in Figure 2 and in the published study protocol [ 13 ]. The study team did not interfere with treatment decisions of the treating physician including drug dosage and schedule because of the observational nature of the study design.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational study was conducted in adult nonpregnant LF patients with mild disease course admitted to and routinely managed at ISTH, the protocol was published previously [ 13 ]. In brief, adult nonpregnant patients with mild disease progression and real-time reverse transcription polymerase chain reaction (RT-PCR)-confirmed LF infection necessitating routine treatment with intravenous ribavirin were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence supporting a beneficial effect of ribavirin for treatment of Lassa fever is scarce, and the pivotal landmark study (2) showed a high risk for bias (5,6). A study focused on evaluation of pharmacokinetics of ribavirin to better characterize its role in treatment for Lassa fever (7). Severe Lassa fever with lethal outcome is associated with encephalopathy, acute kidney injury, and respiratory failure (8).…”
mentioning
confidence: 99%